Does Halal Label Increase Product Sales? - Hafshah Afifah Az-Zuhdiyyah; Aisyah (Universitas Negeri Surabaya, 2024)
This study was conducted to determine whether the halal label increases product sales. The background of this study is because of the large number of MSMEs in Indonesia, especially those engaged in the food and beverage sector, with the government program regarding free halal certificates and the number of Indonesian people with a Muslim majority. This study is qualitative and uses the atlas.ti method to be able to explore data further and review existing literature, as well as make it easier to explore the interview results. With the presence of a halal label on MSMEs, it can help provide branding for a product, so that it can help create higher product sales, although there is no one factor that will increase sales, it can be one of the factors.